Dietary Intake and Biomarkers of α-Linolenic Acid and Mortality: A Meta-Analysis of Prospective Cohort Studies - Chen, Li-Hua; Hu, Qingjing; Li, Guijie; Zhang, Li; Qin, Li-Qiang; Zuo, Hui; Xu, Guangfei (Frontiers in Nutrition, 2021)
ABSTRACT Background: The association between α-linolenic acid (ALA) and mortality is inconsistent and has not been summarized systematically. Objective: The purpose was to conduct a meta-analysis which synthesized the results of prospective cohort studies to investigate associations between ALA intake and mortality. Methods: We conducted a comprehensive search of PubMed, Embase and Web of Science databases through 1 May 2021 for relevant prospective cohort studies which reported associations of ALA (assessed by dietary surveys and/or ALA concentrations in body tissues) with mortality from all-cause, cardiovascular disease (CVD), and other diseases. Multivariable-adjusted RRs were pooled by random- or fixed-effects model. Results: A total of 34 prospective cohort studies, of which 17 reported dietary ALA intake, 14 for ALA biomarkers and the remaining 3 reported both of intake and biomarkers. The studies included 658634 participants, and deaths were classified into all-cause mortality (56898), CVD mortality (19123) and other diseases mortality (19061). Pooled RRs of ALA intake were 0.93 (95% CI: 0.84, 1.01, I2 = 71.2%) for all-cause mortality, 0.90 (95% CI: 0.83, 0.98, I2 = 21.1%) for CVD mortality, and 0.94 (95% CI: 0.83, 1.06, I2 = 73.3%) for other diseases mortality. The two-stage random-effects dose-response analysis showed a linear relationship between dietary ALA intake and CVD-mortality and each 0.5% energy increment of ALA intake was associated with a 5% lower risk of CVD-mortality (RR: 0.95; 95% CI: 0.90, 1.00). Pooled RRs for per SD increment of ALA biomarkers were 0.99 (95% CI: 0.97, 1.01, I2 =27%) for all-cause mortality, 1.00 (95% CI: 0.98, 1.03, I2 = 0%) for CVD mortality and 0.98 (95% CI: 0.95, 1.01, I2 = 0%) for other diseases mortality. Conclusions: This meta-analysis summarizing the available prospective cohort studies indicated that ALA intake was associated with reduced risk of mortality, especially CVD mortality. Our findings suggest that ALA consumption may be beneficial for death prevention.